THE AQIDAH AKHLAK LEARNING MODEL IN THE ONLINE EDUCATION SYSTEM IN THE COVID-19 - Ru’iya, Sutipyo; Masduki, Yusron (Idaarah: Jurnal Manajemen Pendidikan, 2022)
Abstract: The Aqidah Akhlak Learning Model in the Online Education System In The Covid-19 This study aims to reveal the aqidah akhlak learning model in the online learning system during the Covid-19 period. Moral aqidah education is a very important subject in producing students who have noble character. This research method is a qualitative method, with the subject of four teachers from three Madrasah Aliyah Negeri (MAN). The research process starts from data collection with in-depth interviews, data analysis with stages: open coding, axial coding, and selective coding to obtain a significant connecting line which can be a causal relationship or a comparative relationship between phenomena and theory. The last stage is the preparation of theories and conclusions. The results showed that the platforms used in the learning process included: Whatsapp group, Geschool, Google Classroom, Google Meet, and Zoom. The curriculum is an emergency curriculum with essential materials. The teacher prepares the essential material and then shares it through the agreed platform. To improve the smooth learning process, madrasas collaborate with intensive communication with parents and home visits for students with problems. The assessment WhatsApp conducted using an agreed e-learning platform, with a focus on the cognitive domain. Other domain assessments are carried out during the process through assignments.